Attitudes towards single parents' children in private and state-dependent private schools: Experimental evidence - Luis Diaz-Serrano; Sabine Flamand (SERIEs - Journal of the Spanish Economic Association, 2023)
Single parenthood is on the rise worldwide. While acceptance of single-parent households is increasing, some authors point out that single-parent families still suffer from negative societal attitudes compared to heterosexual two-parent families, while also being among the most vulnerable groups of society. Motivated by these findings, we study whether private and state-dependent private schools in Catalonia (Spain) are more reluctant to interact with single parents than with heterosexual couples. We conduct a field experiment during the children's pre-registration period. We create three types of fictitious families (heterosexual couple, single mother, and single father) and send e-mails to schools in which the family structure is made explicit. Our results indicate that schools are more prone to interact with single parents than with heterosexual couples.
Keywords: H41; I20; J12; 330; Children; Discrimination; Field experiment; Schools; Single parents